Ekstraksi dan Identifikasi Komposisi Metabolit Fraksi Diklorometana dan Aquades Ektrak Metanol Daun Sirsak (Annona muricata Linn) - Noviana Mery Obenu (Saintek Lahan Kering, 2019)
Soursop is one of the many plants found in East Nusa Tenggara (NTT). Some parts of the soursop plant are known to have been widely used as traditional medicine or as natural pesticides. The use of plants as a treatment or as a natural pesticide cannot be separated from the bioactive compounds contained therein. These compounds will be successfully isolated depending on the choice of solvent. This research was conducted with the aim of knowing the composition of the metabolites contained in each solvent used. The steps of this study include preparation of soursop leaf samples, extraction by maceration with methanol solvents, partitioning of methanol extract with dichloromethane and water solvents and identification of metabolite compositions with high-performance liquid chromatography (HPLC) instruments. The compounds identified in HPLC dichloromethane solvents are thought to be phenol, polyketide, tannin and alkaloid metabolites. Whereas HPLC identified compounds in water solvents are thought to be polar compounds which are bound to a glycoside group